Yeast nutrient transceptors provide novel insight in the functionality of membrane transporters - Schothorst, Joep; Kankipati, Harish Nag; Conrad, Michaela; Samyn, Dieter R; Van Zeebroeck, Griet; Popova, Yulia; Rubio-Texeira, Marta; Persson, Bengt L; Thevelein, Johan M (Current genetics, 2013)
In the yeast Saccharomyces cerevisiae several nutrient transporters have been identified that possess an additional function as nutrient receptor. These transporters are induced when yeast cells are starved for their substrate, which triggers entry into stationary phase and acquirement of a low protein kinase A (PKA) phenotype. Re-addition of the lacking nutrient triggers exit from stationary phase and sudden activation of the PKA pathway, the latter being mediated by the nutrient transceptors. At the same time, the transceptors are ubiquitinated, endocytosed and sorted to the vacuole for breakdown. Investigation of the signaling function of the transceptors has provided a new read-out and new tools for gaining insight into the functionality of transporters. Identification of amino acid residues that bind co-transported ions in symporters has been challenging because the inactivation of transport by site-directed mutagenesis is not conclusive with respect to the cause of the inactivation. The discovery of nontransported agonists of the signaling function in transceptors has shown that transport is not required for signaling. Inactivation of transport with maintenance of signaling in transceptors supports that a true proton-binding residue was mutagenised. Determining the relationship between transport and induction of endocytosis has also been challenging, since inactivation of transport by mutagenesis easily causes loss of all affinity for the substrate. The use of analogues with different combinations of transport and signaling capacities has revealed that transport, ubiquitination and endocytosis can be uncoupled in several unexpected ways. The results obtained are consistent with transporters undergoing multiple substrate-induced conformational changes, which allow interaction with different accessory proteins to trigger specific downstream events.